A Conceptual Framework for Corporate Governance - Tonk, Mohinder Singh; Arora, D. D. (Prabandhan: Indian Journal of Management, 2011)
Corporate Governance is a wholesome mix of measures that are necessary for creating a corporate culture of accountability and transparency. The term refers to a combination of transparency related practices, laws, rules, regulations, procedures and voluntary initiatives on the part of the companies to maximize the shareholders' long term value and maintain accountability to different stakeholders. These initiatives enhance customer satisfaction, maximize shareholders' value and result in employee delight. The Board of Directors is responsible to the stakeholders for the performance and governance of the business. It has been seen over the years that business organizations that measure up to the expectations of the stakeholders in the arena of corporate governance are rewarded with loyalty by different stakeholders and are looked upon as responsible corporates.